O perfil da mortalidade adulta por idade e causas básicas de óbito na América Latina e Caribe (2000 – 2010) - Júlia Almeida Calazans (2015)
Since the 1930s, the Latin American and Caribbean have experienced a rapid decline in mortality levels, along with a progressive shift of morbidity and mortality patterns by age and by causes-of-death, known as "epidemiological transition". The main aim of this study is to analyze the profile of adult mortality by age and causesof-death (diabetes, cardiovascular diseases, neoplasms, infectious diseases and HIV/AIDS) in Latin America and the Caribbean (Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Mexico, Peru and Uruguay), between 2000 and 2010, considering the major changes in the epidemiological profile that have been occurring in all countries of this region. More specifically, it aims to: (1) analyze the main changes in the probability of survival and in the average number of years lived between 15 and 60 years; (2) analyze the main changes in adult survival by age group; (3) analyze the effect of each cause-of-death on survival probability and on the average number of years lived into adulthood, and (4) contextualize the epidemiological profiles found within the theoretical framework of epidemiological transition. The probability of survival and the average of years lived are calculated from multiple decrement life tables. Mortality rates used as an input in these tables were calculated from the death information provided by the World Health Organization and from the population estimation by the United Nations. These rates were adjusted by subenumeration using the Combined Extinct Generations method. The results show that adult mortality levels are very different across countries, but the mortality pattern by cause-of-death is very similar, indicating that Latin America and the Caribbean are in an intermediate stage of classical epidemiological transition proposed by Omran, with a predominance of chronic degenerative diseases such as cardiovascular diseases and neoplasms. For men, the results also emphasize the importance of external causes for adult mortality. We conclude that potential future gains in longevity will depend on health policies focused on handling chronic conditions and on the creation of multisector policies that face violence both as a social and a public health problem.